Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1631/jzus.b1300034
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of enamel bond strengths for conventional and resin-modified glass ionomers: acid-etching vs. conditioning

Abstract: Abstract:Objective: This study deals with the effect of phosphoric acid etching and conditioning on enamel micro-tensile bond strengths (μTBSs) of conventional and resin-modified glass ionomer cements (GICs/RMGICs). Methods: Forty-eight bovine incisors were prepared into rectangular blocks. Highly-polished labial enamel surfaces were either acid-etched, conditioned with liquids of cements, or not further treated (control). Subsequently, two matching pre-treated enamel surfaces were cemented together with one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…With respect to the shear bond strengths of the GICs with extracted human teeth, studies have shown that phosphoric acid etching can dramatically increase the enamel micro-tensile bond strengths (μTBSs) of conventional GICs and resin-modified GICs 39) . Porous structures may be formed on the enamel surface after etching.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the shear bond strengths of the GICs with extracted human teeth, studies have shown that phosphoric acid etching can dramatically increase the enamel micro-tensile bond strengths (μTBSs) of conventional GICs and resin-modified GICs 39) . Porous structures may be formed on the enamel surface after etching.…”
Section: Discussionmentioning
confidence: 99%
“…Although GIs can bond to enamel even in the presence of a smear layer, bond strength can be increased by pretreatment with a surface conditioner (such as PA, citric acid, maleic acid, or polyacrylic acid) to remove the smear layer 32,33) . PA etching of the tooth surface provides good wetting of the surface and enables GIs to chemically interact with the mineral phase of enamel by ionic 34) interaction. Polyalkenoic acids have been shown to be irreversibly adsorbed onto hydroxyapatite surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine teeth make it easier to standardize the samples, with a lower risk of infection, besides the bioethical issues (Wang et al 2012;Zhang et al 2013). They present similarities to the human dental tissues, particularly concerning the orientation of the enamel prisms, an equivalent percentage by weight of calcium, and protein matrix composed of the same amino acids (Wang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As regards dentin, there are some controversies relative to the similarity between the teeth of both species. However, there is a consensus in the literature that in shallow cavities, with a depth of 2 mm, bovine dentin has been shown to be feasible for adhesion, providing adequate bond strength when compared with human dentin (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%